Análise do funcionamento diferencial dos itens do competitive State anxiety inventory-2 - Bartholomeu, Daniel; Montiel, José Maria; Da Silva, Marjorie C. R.; Machado, Afonso Antonio [UNESP]; Cecato, Juliana Francisca; Pinheiro, Luan T. E. (My University, 2015)
The present study investigated the differential item functioning of the Competitive State Anxiety Inventory-2 items by sex in a sample of athletes searching for bias. 172 athletes, 61.6% males, aged 14-58 years old were investigated. The sports were basketball (14.5%), soccer (28.5%), Handball (22.7%), Jiu-jitsu (13.4%) and volleyball (20.9%), and the research was performed in various clubs and teams in São Paulo. We analyzed the items and persons fit to the Rasch model and a few misfits were identified. That is, in some items, high concordance of low anxiety people occurred and vice versa. The differential item functioning by sex suggested approximately 40% of biased items to one of the groups and especially men were favored. New studies must be alert to this fact, avoiding problems regarding the validity of the instrument.
Keywords: Assessment psychological; Human performance; Psychodiagnostic